THE "SOUTHERN GREAT WALL OF CHINA" IN FENGHUANG COUNTY: DISCOVERY AND RESTORATION. (September 2013) - Yonglin, Jiang
Abstract : In the English-speaking world, it is widely known that, during the late sixteenth and early seventeenth centuries, China's Ming dynasty (1368–1644) intensified its efforts to the construction of the Great Wall (" changcheng " 長城, aka " bianqiang" 邊牆 [border wall] in Chinese documents) along its northern frontiers, which handed down the legacy of the Great Wall of China. 1 It is little known, however, that during the same time period the government of Huguang Province of the Ming also built a "border wall" (bianqiang 邊牆 ) besieging the Laershan 臘爾山 "Miao territory" (Miaojiang 苗疆 ) in the southern part of the empire, especially at the present-day Fenghuang County 鳳凰縣, Xiangxi Autonomous Prefecture of Tujia Nationality and Miao Nationality 湘西土家族苗族自治州, Hunan Province (Figure 1 ). Compared to the world-renowned Great Wall in the north, the border wall in the south, or the "Southern Great Wall" (nan[fang] changcheng 南 [ 方 ] 長城 ) as promoted in China today, has attracted little scholarly attention in the English literature. 2 Yet, the less impressive undertaking is no less significant in revealing the enduring process of identity building in China during both imperial times and the People's Republic. In recent years, with the assistance of local residents, I visited the sites of the "Southern Great Wall" and a number of Miao communities along and outside the wall, including the areas in both Fenghuang in West Hunan and Songtao Autonomous County of Miao Nationality 松桃苗族自治縣 in east Guizhou. It is my intention that this fieldwork report regarding the discovery and restoration of the border wall will bring a wider scholarly attention to this cultural site for a richer study of the identity building and cultural experience in this Miao territory.